Degradation of benzotriazole by sulfate radical-based advanced oxidation process. Issue 2 (15th January 2021) - Ma, Jie; Ding, Yi; Chi, Liping; Yang, Xin; Zhong, Yingjie; Wang, Zhiheng; Shi, Quan
ABSTRACT: Benzotriazole (BTA) is a recalcitrant contaminant that is widely distributed in aquatic environments. This study explored the effectiveness of sulfate radical-based advanced oxidation process in degrading BTA (SR-AOP). The sulfate radical was generated by heat activation of persulfate (PS). Our results show alkaline pH promoted the BTA degradation. The solution pH also affected the speciation of total radicals. Sulfate radical ( S O 4 ⋅ − ) predominated at acidic pH while hydroxyl radical (HO ) predominated at basic pH. High temperature, high PS concentration and low BTA concentration promoted the BTA degradation. Influence of water matrix constituents on the reaction kinetics was assessed. We found that ≤10 mM of Cl − promoted the reaction, but 100 mM Cl − inhibited it. H C O 3 − was similar to Cl − . Br − and C O 3 2 − inhibited the reaction while S O 4 2 − did not affect the reaction. N O 3 − of ≤10 mM did not affect the reaction, but 100 mM of N O 3 − inhibited it. Eleven degradation intermediates were identified using ultra-high solution Orbitrap mass spectrometry. Based on the intermediates identified, possible reaction pathways were proposed. Overall, SR-AOP can effectively mineralize BTA, but water matrix constituents greatly influenced the reaction kinetics and thus should be carefully considered for its practical application. Abbreviations: BTA, benzotriazole; PS, persulfate; PMS, peroxymonosulfate; SPC, sodium percarbonate; AOP, advanced oxidation process; PS-AOP, persulfate-based advanced oxidation process; SR-AOP, sulfate radical-based advanced oxidation process; TAP, thermally activated persulfate; TOC, total organic carbon; TBA, tert-butyl alcohol GRAPHICAL ABSTRACT: UF0001